2018
DOI: 10.3390/ijerph15010102
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Residential Green Space on Infantile Atopic Dermatitis Associated with Prenatal Air Pollution Exposure

Abstract: Few birth cohort studies have examined the role of traffic-related air pollution (TRAP) in the development of infantile atopic dermatitis (AD), but none have investigated the role of preventive factors such as green spaces. The aim of this study was to investigate whether exposure to nitrogen dioxide (NO2) and particulate matter with an aerodynamic diameter of <10 μm (PM10) during pregnancy is associated with increased risk of development of AD in 6-month-old children and also to examine how this association c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 43 publications
(57 reference statements)
1
25
0
Order By: Relevance
“…In particular, AD got worse in spring with high levels of styrene, in summer with high levels of toluene and NO2, in autumn with high levels of volatile organic compounds, and in winter with high levels of fine particulate matter [80]. These data were confirmed by other researches [8488].…”
Section: Environmental Factorssupporting
confidence: 68%
“…In particular, AD got worse in spring with high levels of styrene, in summer with high levels of toluene and NO2, in autumn with high levels of volatile organic compounds, and in winter with high levels of fine particulate matter [80]. These data were confirmed by other researches [8488].…”
Section: Environmental Factorssupporting
confidence: 68%
“…However, with an odds ratio of 1.05 and the small quantity of observational, cohort studies, and individual studies, the statistical power of this meta-analysis is limited. Several new studies have been published that were not included in this meta-analysis [54][55][56][57][58][59][60]. More recently, Krämer and co-workers have reviewed this evidence by combining data from 57 environmental epidemiological studies in a systematic review [61].…”
Section: Epidemiologymentioning
confidence: 99%
“…In addition, a study conducted in the Munich metropolitan area revealed a strong positive association between the distance to the nearest main road and eczema; in particular, it was found that NO 2 was positively associated with eczema in children exposed to traffic‐related air pollution . In a more recent work, PM 10 and NO 2 exposure during the first trimester of pregnancy was associated with the development of infantile AD . It has also been demonstrated that maternal smoking during pregnancy and/or in the first year after birth is a major risk factor for the development of AD among children aged between 6 and 13 years .…”
Section: Pollution and Skin Pathologiesmentioning
confidence: 96%
“…19 In a more recent work, PM 10 and NO 2 exposure during the first trimester of pregnancy was associated with the development of infantile AD. 20 It has also been demonstrated that maternal smoking during pregnancy and/or in the first year after birth is a major risk factor for the development of AD among children aged between 6 and 13 years. 21 Similarly, fetal tobacco smoke exposure during the third trimester of pregnancy was positively associated with a higher cumulative incidence of atopic eczema/dermatitis syndrome in exposed infants in a Japanese study; the authors suggest that maternal smoking might induce epigenetic changes in the fetal allergen-specific immune responses, promoting development of AD.…”
Section: Cutaneous Tissues As a Gateway For The Outdoor Pollutantsmentioning
confidence: 99%